Prevalence and clinical correlates of clinical red flags for rare diseases in consecutive patients presenting with HCM phenotype. (3rd October 2022) - Maurizi, N; Dall'aglio, G; Fumagalli, C; Argiro, A; Olivotto, I
Abstract: Introduction: For patients presenting with primary Left Ventricular Hypertrophy (LVH), the ESC recommends systematic search for diagnostic clues or "red flags" (cardiac and non-cardiac) that can identify particular treatable disorders and guide rational selection of diagnostic tests. To date, a systematic evaluation of this recommendation has not been performed Purpose: We sought to determine prevalence and predictive accuracy of clinical markers (red flags, RF), known to be associated with specific systemic disease in a consecutive cohort of patients with hypertrophic cardiomyopathy (HCM). Methods: We studied 210 consecutively genotyped patients (54±21 years, 118 (56% males) referred to our center for the suspicion of primary LVH. Pre-specified RF were categorized into four domains: family history; signs/symptoms; electrocardiography and imaging. Results: Of the 210 patients, 84 (40%) were diagnosed with sarcomeric HCM, 56 (27%) with TTR amyloidosis, 44 (21%) with Fabry disease (FD), 7 (4%) with a mitochondrial disease, 4 (2%) with Pompe disease, 4 (2%) with PRKAG2 cardiomyopathy, 3 (1%) with Noonan, 3 (1%) with Friederich's Ataxia, 3 (1%) with LEOPARD and 2 (1%) with Danon disease. A total of 942 RF has been identified in the cohort. Concerning family history, autosomal dominant pattern was specific for sarcomeric HCM (66/84, 79%), whereas X-linked inheritance was frequently observed in Fabry disease (40/44, 91%). Non-sarcomeric causes of HCM were the most prevalent in ages <1yo and >55yo. Ophthalmological signs/symptoms (22/23) were specifically find in FD, whereas muscolo-skeletal RF were rare and non-specific. Neurological phenotype was prevalent in FD patients (38/44, 86%), as well as in TTR amyloidosis (carpal tunnel in 29/56, (52%)), in mithocondropathies and Friederich's Ataxia. Cutaneous involvement was frequent in FD (12 patients with angiokeratomata) (Tab.1). Giant T waves inversion was the most prevalent ECG alteration, but aspecific (61 patients, 32/84 sarcomeric HCM, 16/44 FD). Short PR interval was found in 24 (12%) of patients and specific for FD (15/44) and mitochondrial disease (3/7). Low QRS voltage was present in 17 (8%) patients, and of these 16 had TTR amyloidosis. Inferior leads Q waves was uncommon and non-specific. Mitral valve disease (SAM and anterior mitral leaflet elongation) and apical LVH were present respectively in 57/210 (28%) and 9/210 (4%) of the patient and were almost entirely observed in sarcomeric HCM. Concentric LVH and severe left posterior wall hypertrophy were extremely specific for non sarcomeric HCM (108/109 cases). Strain apical sparing was useful in the identification of TTR amyloidosis. Conclusions: Clinical RF in patients with primary LVH are common and can be highly specific for correct phenotypisation of the patient. An extensive diagnostic work-up should therefore be conducted by the physician to identify potentially treatable primary LVH causes. Funding Acknowledgement: Type of funding sources: None.